2008
DOI: 10.1002/jmv.21381
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic mutations associated with attenuation and changes in tropism of Urabe mumps virus

Abstract: Although several effective mumps virus vaccines have been developed, almost nothing is known about the genetic changes responsible for loss of virulence. One vaccine, Urabe AM9, was withdrawn from the market because of insufficient attenuation. The vaccine was found to contain a mixture of viruses that could be distinguished based on the sequence of the hemagglutinin‐neuraminidase gene (HN). Viruses containing lysine at HN amino acid position 335 were isolated from cases of post‐vaccination parotitis or mening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 51 publications
(74 reference statements)
0
14
0
Order By: Relevance
“…[28] recombinant viruses containing either K or E at position 335 showed similar neurotoxicity in the newborn rat model. Furthermore, Shah et al [29], identified fifteen additional genetic differences which might be responsible for difference in virulence. Sauder et al [30], argued that searching for markers of virulence based on the consensus sequence only might be misleading and showed that the level of genetic heterogeneity at specific genome sites can have profound neurovirulence phenotypic consequences.…”
Section: Discussionmentioning
confidence: 98%
“…[28] recombinant viruses containing either K or E at position 335 showed similar neurotoxicity in the newborn rat model. Furthermore, Shah et al [29], identified fifteen additional genetic differences which might be responsible for difference in virulence. Sauder et al [30], argued that searching for markers of virulence based on the consensus sequence only might be misleading and showed that the level of genetic heterogeneity at specific genome sites can have profound neurovirulence phenotypic consequences.…”
Section: Discussionmentioning
confidence: 98%
“…For example, the Urabe strain of mumps vaccine (discontinued due to neurovirulence) contains subpopulations that differ in the sequence of the hemagglutinin-neuraminidase gene and the propensity to cause meningitis post-vaccination [54]. The yellow fever 17D vaccine is also a mixed population, and it contains subpopulations with different plaque morphology and reactivity with monoclonal antibodies [11].…”
Section: Genetic Instabilitymentioning
confidence: 99%
“…Further, it was shown that Urabe-AM9 strain is constituted by several virus quasispecies that differ in distinct sites all along their genome, with several amino acids changes in the NP, P, L (involved in replication/transcription), F and HN proteins (involved in the recognition, fusion and release of virus in infected cells), as well as in the intergenic region NP-P (Shah et al, 2009). Sauder et al, showed that genetic heterogeneity at the specific genome sites have a profound effect on the neurovirulent phenotype of Urabe-AM9 strain (Sauder et al, 2006), suggesting there is not a unique genetic marker responsible for virus attenuation, rather the combination of mutations may be necessary for an adequate viral attenuation (Amexis et al, 2001;Sauder et al, 2006;Shah et al, 2009). …”
Section: Genetic Characterization Of Post Vaccination Virus Isolates mentioning
confidence: 99%
“…Using a rat based model of mumps neurovirulence, Shah et al demonstrated that viral variants with a Glu at position 335 of HN glycoprotein is significantly attenuated (hydrocephalus 1.37% ± 0.50) compared to a virus isolated from a patient with postvaccination meningitis (hydrocephalus 4.70%±0.77) and compared with wild type (hydrocephalus 11.47%±1.16) which have Lys at this position (Shah et al, 2009). …”
Section: Structural Functional and Antigenic Analysis Of Mumps Virusmentioning
confidence: 99%